Fostering e-commerce in the light of the Deep and Comprehensive Free Trade Area (DCFTA): A case study of Georgia - Tamta Margvelashvili (Journal of Law, 2020)
E-commerce by constituting a revolutionary shift from a traditional business model to an Internet-based economic structure has influenced the way commerce is done in the 21st century. While e-trade promotes an economic enhancement by offering unlimited access to global markets with less operational costs and increased productivity, state legislators find it difficult to align their policies with ever-changing technologies. Although applying laws to e-commerce transactions is to certain degree settled in the developed world, developing countries are considerably lagging behind in their experiences. To address this deficit, the present paper analyzes the e-commerce structure, its deployment strategies, and the legal implications thereof. It argues that e-commerce serves as a strong basis for macro and micro economic growth and, therefore, it should be thoroughly embraced by third countries[1] especially in the aftermath of the Covid-19 pandemic when the governments are trying to preserve its economy by switching businesses to online platforms. Nevertheless, the adoption and implementation of e-trade should occur in a systemic manner with corresponding legal ramifications at national and international levels. In order to enrich the paper with some practical insights, this research introduces a case-study of Georgia as a part of Eastern Partnership countries. It presents relevant provisions of the Association Agreement concluded between the European Union and Georgia, as an underlying basis for e-commerce deployment in the country. Where applicable, the paper also looks at the national legislation and further uncovers issues that are likely to emerge for Georgia in the course of adopting a new framework.